Percutaneous and surgical management of aortic stenosis in the SWEDEHEART registry (2013–2023) : a nationwide observational study - Tödt, Johannes ; 0009-0006-8083-1120; Koul, Sasha; Yndigegn, Troels; Angerås, Oskar; Bjursten, Henrik; Nozohoor, Shahab ; 0000-0002-5786-864X; Friberg, Örjan; Backes, Jenny; James, Stefan; Redfors, Björn; Gilje, Patrik; Labaf, Ashkan; et al. (The Lancet Regional Health - Europe, 2026)
Background: Management of severe aortic stenosis (AS) has evolved over the past decade, driven by the widespread adoption of transcatheter aortic valve implantation (TAVI). This study aims to assess trends in procedural volumes, patient characteristics, and outcomes for patients undergoing TAVI or surgical aortic valve replacement (SAVR) in Sweden. Methods: This was a descriptive, non-comparative, nationwide cohort study using the SWEDEHEART registry. We included 21,383 patients who underwent TAVI or SAVR between 2013 and 2023 (11,366 TAVI and 10,017 SAVR). Trends in patient characteristics, preoperative risk, complications and mortality were examined. Findings: TAVI procedures increased from 307 (26.1%, n = 307/1174) in 2013 to 1851 (71.2%, n = 1851/2601) in 2023, while SAVR volumes declined from ∼1000 annually before 2018 to roughly 750 procedures annually. Median age of TAVI patients were 81 (IQR 77, 85) years and 71 (IQR 65, 76) years for SAVR patients. The median EuroSCORE II for TAVI decreased from 5.6 (IQR 3.3, 10.2) to 2.7 (IQR 1.7, 4.6) (p = 0.002), and STS-PROM from 3.3 (IQR 1.9, 4.1) to 1.6 (IQR 1.1, 2.8) (p = 0.0021). Among SAVR patients, EuroSCORE II decreased from 1.5 (IQR 1.0, 2.3) to 1.3 (IQR 0.9, 2.1) (p = 0.022) and STS-PROM from 1.8 (IQR 1.2, 3.0) to 1.6 (IQR 1.1, 2.6) (p = 0.0082). Any in-hospital complications declined significantly for TAVI (29.2%, n = 210/719 to 13.2%, n = 244/1851), while SAVR complication rates increased slightly (18.4%, n = 354/1921 to 18.7%, n = 140/750). In-hospital mortality for TAVI declined from 3.6% (n = 26/719) to 1.0% (n = 18/1851), and 1-year mortality from 11.1% to 6.9% (p = 0.019). SAVR in-hospital all-cause death decreased from 1.6% to 0.4% (n = 3/750) and 5.0% to 2.2% for 1-year mortality (p = 0.013). Interpretation: TAVI has become the predominant treatment strategy for AS in Sweden expanding access within the treated cohort. Despite this, current 2023 SAVR results demonstrate similar in-hospital complication rates compared to TAVI (18.7% vs 13.2%), but lower in-hospital (0.4% vs 1.0%) and 1-year mortality rates (2.2% vs 6.9%). Funding: This study was supported by ALF and national research funding bodies.
Publisher Copyright: © 2025 The Author(s)
Keywords: Aortic stenosis; Aortic valve implantation; Prosthetic aortic valve implantation; SCSR; Surgical aortic valve replacement (SAVR); SWEDEHEART; SWENTRY; Temporal trends; Transcatheter aortic valve implantation (TAVI); Valve replacement outcomes